The Peace Imperative for the Sendai Framework for Disaster Risk Reduction - Laura E. R. Peters (International Journal of Disaster Risk Science)
Abstract Disasters disproportionately affect conflict-affected regions, where approximately two billion people reside, posing significant challenges for disaster risk reduction (DRR). This reality has increasingly spurred calls for violent conflict to be included in the global DRR agenda. However, consideration of peace has been lacking, despite that challenges for peace can distinctly impact capacities to set, pursue, and achieve DRR objectives. This study investigated how the Sendai Framework for Disaster Risk Reduction 2015–2030 (SFDRR) engages with peace through a document analysis, revealing three key findings. First, the SFDRR does not mention “peace,” mirroring its lack of reference to conflict. Second, while peace-related terms appear throughout the SFDRR in themes related to partnership and all-of-society approaches, this engagement is superficial. Third, the SFDRR’s approach is fundamentally problematic for advancing peace due to its avoidance of the complex social and political dynamics inherent to disaster risk and its reduction. The SFDRR united United Nations Member States in its ambition to “leave no one behind,” but has taken approaches that smooth over diversity rather than strengthen pluralistic connections. A radical, integrated DRR-peacebuilding agenda must take conflict as the new starting point and carve new pathways toward peace including through disaster diplomacy and environmental peacebuilding. By embracing the ambiguity between war and peace and addressing the root causes of risk, societies can cultivate peaceful interactions and collectively advance safety. This study concludes with recommendations for a global DRR policy that not only implicitly relies on peace but actively contributes to peacebuilding in the world’s diverse and divided societies.